An Approach to the Optimization of Mobile Payments for the Transport System using (NFC) through Cloud Computing - Gómez Torres, Estevan; Herrera-Herrera, Nelson; Díaz, Magí Paúl (Enfoque UTE, 2017)
The use of mobile devices has gradually increased. Every day, the number of organizations adopting systems which include some type of mobile payments is becoming bigger. Because of this reason, it is mandatory to have agile and quick systems to guarantee security and reliability, not only for the user but also for the operator. In that way, users will get a high-quality service based on mobile technologies. An analysis of NFC Technology has been made in this paper taking into consideration a proposal of a system development including mobile payments, which could be used in the transportation system of Metro of Quito. To assure the response time and transactional security, the use of cloud computing is recommended.